Promoting an African foods systems agenda at COP28 - Chevallier, Romy; Trautman, Sabrina; Gosling, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
At the 28th Conference of the Parties (COP28), it is imperative for African countries to foster unity and collaboration with other developing nations to realise successful outcomes for the continent’s food systems transformation agenda. Key resources for the Africa Group of Negotiators and other stakeholders include the African Union Climate Change and Resilient Development Strategy (2022-2032) (African Union Climate Strategy) and the Nairobi Declaration to identify concrete priorities and actions for climate-resilient agriculture in Africa. The Eastern Africa Farmer’s Federation (EAFF) has issued a Call to Action for COP28, outlining priority action areas crucial for advancing Africa’s food systems. These priorities include: i) advocating for significant progress in the agricultural negotiating track of climate negotiations; ii) ensuring that adaptation remains a focal point in all COP28 decisions and initiatives; iii) promoting the inclusion of agricultural targets in the Global Goal on Adaptation; iii) substantially increasing financing to support climate action in agri-food systems; iv) guaranteeing the Loss and Damage Fund provides adequate support to frontline communities and secures financial pledges; and, urgently enhancing ambition and increasing the overall global collective effort to climate change. This policy insight draws upon these priority action areas and other cross-cutting issues, describing the relevant commitments and intervention areas given in the Nairobi Declaration and the AU Climate Strategy, to support and strengthen the case for Africa's climate resilient food systems transformation agenda at COP28.